1978
DOI: 10.3109/01485017808988337
|View full text |Cite
|
Sign up to set email alerts
|

Factors Underlying Infertility in the Alcoholic

Abstract: In an effort to identify the factor(s) contributing to loss in sexual competence in alcoholics, a pilot study was made of the interrelationships of hepatic disease, plasma hormone levels and importnce in 35 male patients in an alcohol unit. Contrary to previous reports, impotence was not a direct concomitant of hepatic disease, elevated sex hormone-binding globulin capacity or hyperestrinism. The most significant aberration found was a nearly 30% lower mean free testosterone concentration which appeared to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 3 publications
0
0
1
1
Order By: Relevance
“…In the present study no significant difference in the serum testosterone concentration was observed when alcoholic cirrhotics with and without sexual dysfunction were compared. It has been suggested that the nonprotein-bound and not the total testosterone concentration is associated with impotence in male alcoholics (21), but again we observed no significant difference concerning the non-proteinbound testosterone concentration in alcoholic cir-rhotics with and without sexual dysfunction. Before rejecting a relation between serum testosterone concentrations and sexual function, however, larger patient groups should be studied.…”
Section: Discussioncontrasting
confidence: 69%
“…In the present study no significant difference in the serum testosterone concentration was observed when alcoholic cirrhotics with and without sexual dysfunction were compared. It has been suggested that the nonprotein-bound and not the total testosterone concentration is associated with impotence in male alcoholics (21), but again we observed no significant difference concerning the non-proteinbound testosterone concentration in alcoholic cir-rhotics with and without sexual dysfunction. Before rejecting a relation between serum testosterone concentrations and sexual function, however, larger patient groups should be studied.…”
Section: Discussioncontrasting
confidence: 69%
“…I1 enest de m~me de Ia testost6rone totale. De m~me, la diminution de la testost6rone totale et de sa fraction libre [7], une augmentation de la SHBG s6rique [3] ont 6t6 raises en 6vidence dans un groupe de patients alcooliques atteints de dysfonction 4rectile. Dans l'h6mochromatose, l'hypogonadisme li6 g~ l'atteinte gonadique entraine une augmentation de la SHBG s6rique [4].…”
Section: Introductionunclassified